SARCOMAS: CURRENTTRENDS IN DIAGNOSISANDTREATMENT (Uzbekistan Open Conference, 2025)
The study of sarcomas is important for modern medicine, as these tumors are characterized by their complex nature and aggressive course. Sarcomas arise from connective tissue and can affect bones, muscles, blood vessels, and internal organs. Understanding the causes and mechanisms of their development helps to identify factors contributing to malignant cell degeneration. Research is aimed at improving early diagnosis methods, which increases the chances of successful treatment. The development of new therapeutic approaches, including targeted and immunotherapy, helps to reduce mortality. Studying sarcomas also deepens knowledge about the behavior of tumor cells in general and helps in the fight against other types of cancer.